Strategic plan for the Industrial & Commercial Bank of China (ICBC) Peru - Liu, Yuwei (2019)
The purpose of this thesis is to present a Strategic Plan for the Industrial & Commercial Bank of China (ICBC) Peru, with a vision for 2030, when the bank should become a preferred, profitable, secure, and innovative financial institution with a focus on bilateral business between Peru and China. D’Alessio’s (2008), The Sequential Model of the Strategic Process, was adopted for the planning; ICBC Peru’s public reports and interviews to its employees have been used to acquire relevant information. Firstly, ICBC Peru’s vision, mission, and so on, are defined and then, the external and internal conditions are analysed. Opportunities, threats, strengths, and weaknesses are then identified through Tridimensional, Porter’s Diamond, PESTE, Five-Forces, AMOFHIT, and so on, and have been used in SWOT to generate twelve strategies, from which eight are retained through SPACE, BCG, IE, and GS analysis. The vision is then divided into actionable long-term objectives to combine with the 5 strategies to generate short-term objectives and their respective conditions, such as organizational structures, policies, evaluation tools for the implementation and revision. The main findings for ICBC Peru in this thesis are: the main opportunities, externally, are the likely future growth of Peru’s GDP, internal demand, and investment; and the main threats are corruption, governmental administrative capacity, and natural disasters; internally, the main strength is the group support; and the main weaknesses are the small equity and lack of effective localization. The eight retained strategies need to solve this external and internal situation by means of: diversification (retail banking & tailored services), market penetration (more marketing), alliance with local banks (localization), and product development (Fintechs introduction).